تطوير نظام تأهيل مسبق للتعاقد على مشروعات القطاع الحكومي بطريقة تصميم - بناء - حمد, ابتسام; مصطفى, ماهر; علي, كنز (Latakia University Journal -Engineering Sciences Series, 2018)
The successful of implementation the engineering contracts mainly depends on awarding these contracts only to entities that have appropriate expertise and capacity to implement them. Pre-qualification is the process of checking the availability of expertise, technical, administrative and financial capacities of these entities according to the requirements of the project. In this research, a pre-qualification system for design-build projects was constructed. The criteria for this system were obtained through previous studies, international experiments and interviews with a number of experts. The total number of these criteria reached to 68, divided into 11 main criterion under each of them several levels of sub-criteria. Then, weights of these criteria were calculated by using Fuzzy AHP method. After that, an integrated system was built to calculate the grades that design-build contractor deserve for each criterion, using the opinions of a number of experts and specialists in the field of research. In order to facilitate the use of this model, it was programmed on the computer using EXCEL VBA إن تحقيق النجاح في تنفيذ العقود الهندسية بمختلف أنواعها يعتمد بشكل أساسي على منح هذه العقود فقط إلى كيانات تمتلك الخبرات والقدرات الملائمة لتنفيذها، والتأهيل المسبق هو عملية التحقق المسبق من مدى توافر الخبرات والقدرات الفنية والإدارية والمالية لدى هذه الكيانات وفقاً للمتطلبات الخاصة بالمشروع. تم في هذا البحث اقتراح نظام تأهيل مسبق خاص بمشروعات التصميم-بناء حيث تم الحصول على المعايير الخاصة بهذا النظام من خلال الدراسات السابقة والتجارب العالمية والمقابلات الشخصية مع عدد من الخبراء، وقد بلغ إجمالي عدد هذه المعايير 68 معياراً تم تقسيمها إلى 11 معيار رئيسي ينطوي تحت كل منها عدة مستويات من المعايير الفرعية. ثم بعد ذلك تم حساب أوزان هذه المعايير باستخدام أسلوب التحليل الهرمي الضبابي Fuzzy AHP وذلك عن طريق الاستعانة بعدد من الخبراء لإجراء المقارنات الثنائية فيما بين المعايير. وبعد ذلك تم بناء نظام متكامل لاحتساب الدرجات التي يستحقها طالبو التأهيل عن كل معيار من المعايير. ولغرض تسهيل عملية استخدام هذا النموذج فقد تمت برمجته على الحاسب باستخدام (EXCEL VBA).